Seasonal variation of serum potassium in hemodialysis patients: myth or reality? A narrative review of literature - Zhe Bai; Gang Lu; Hengchao Yang; Dahao Zhang; Yuanyuan Zhang; Zuoya Sun (Renal Failure)
Research has shown that patients undergoing hemodialysis experience seasonal variations in their serum potassium levels. There was inconsistent seasonal fluctuation in serum potassium levels among the hemodialysis population across different locations. In the form of narrative review for the first time, the article discusses the seasonal changes of serum potassium in this population and its potential reasons, this article demonstrates that it is primarily attributable to seasonal dietary potassium intake. However, existing studies have not quantified seasonal dietary potassium intake, so the results are still speculative. Furthermore, future research ought to further expound upon the clinical implications of seasonal variations in serum potassium levels among dialysis patients, as well as other influencing mechanisms such as the pathophysiological causes of these seasonal changes, particularly those pertaining to dietary, geographical, and regional factors. These findings contribute to a more thorough interpretation of laboratory results in hemodialysis patients and provide important guidance for their individualized dietary management.